PERLINDUNGAN HUKUM TERHADAP PERKAWINAN ANAK DI BAWAH UMUR MENURUT UNDANG-UNDANG PERLINDUNGAN ANAK (STUDI PENETAPAN PENGADILAN AGAMA NOMOR 23/PDT.P/2020/PA.SPT DAN PENETAPAN NOMOR 0391/PDT.P/2016/PA.CBN) - Febrian Rizky Firmansyah; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
Legislation is one of the legal instruments to protect the public. Marriage dispensation is the domain of the Marriage Law which lex specialis regulates the granting of the right for someone to marry even though they have not reached the required age limit. Meanwhile, the UUPA as lex generalis has condemned the occurrence of child marriages. Marriages of minors often occur due to court decisions, so the problem arises how the judge considers the marriage of minors in the determination of Number 23/PDT.P/2020/PA.SPT and Number 0391/Pdt.P/2016/Pa.Cbn?, and how is the granting of a marriage dispensation linked according to the provisions of the Child Protection Act? The research method used is normative juridical with a case approach and legislation. Based on the results of the analysis, the judge's consideration of the marriage of minors in the two cases of determining the marriage dispensation is more focused on preventive nature. Through these preventive legal considerations, it will provide benefits (benefits) and avoid harm from things that are unwanted and prohibited by religion. The provision of marriage dispensation through the determination of the Religious Courts for minors is not a form of protection for children, but rather provides an opening for every child who is not yet an adult to be able to carry out marriages. Based on legal rules, general provisions override special provisions so that the marriage dispensation regulated in the Marriage Law will override the UUPA.